Determinan Perilaku Remaja Putri dalam Personal Hygiene Masa Haid - Irfiah, Irfiah (Jurnal Kesehatan, 2024)
The clean living behaviour of young women during menstruation could be affected by several factors related to personal hygiene in their daily lives. The research aims to determine the behaviour of young women's hygiene during menstruation. The analytical observational research design uses a cross-sectional approach. The population was 84 and calculated using the Slovin formula to be 70 young women and using simple random sampling. The research period is November to December 2023, with the independent variables being knowledge, beliefs, attitudes, infrastructure, and support from friends, as well as the dependent variable of adolescent behaviour in personal hygiene during menstruation. Data analysis was carried out univariately on each variable and bivariately on the independent variable, specifically the dependent variable, using the ordinal regression statistical tests. The data analysis showed that the variables of friend support and infrastructure influence the behaviour of young women with a significance of 0.041<0.05 (friend support) and 0.000<0.05 facilities and infrastructure. Besides, knowledge, beliefs, and attitudes do not affect the behaviour of young women, resulting in a significance of 0.339, 0.446, and 0.623 (knowledge, beliefs, and attitudes).